Comparison of crude oil price transmission to food commodities for biofuel source and non-biofuel source - Wijayati, Prasmita Dian; Rachmadhan, Aditya Arief; Rizkiyah, Noor (AGROMIX, 2024)
Introduction: World crude oil prices are linked to food commodity prices as input costs for the production distribution and development of biofuels. The relationship between increasing crude oil prices and food prices is in one way; i.e. an increase in world crude oil prices will trigger an increase in food prices and not the other way around. This study aimed to analyze and compare price transmission and integration of cross-commodity prices between the price of crude oil and the price of corn (raw material for biofuels) and the price of rice (non biofuels raw material). Methods: This study used the VARX (Vector Autoregression with Exogenous variables) method with corn prices and rice prices as the endogenous variables, while crude oil prices as exogenous variables. Results: Price transmission and integration of cross-commodity prices occur in crude oil to corn commodities. In contrast, there was no price transmission and price integration between crude oil and rice. Commodities that are directly related to the development of biofuels experience a more significant impact on price changes. Conclusion: Energy commodity prices are connected to food commodity prices, particularly corn. Therefore, if crude oil price rises, so does the corn. Highly dependent corn-importing countries have to be aware. Measures engendering food security are key to any country, particularly promoting domestic production and improving food storage and distribution systems to reduce the risk of food price spikes. The policy implications emerging from the one-directional causality between oil and food prices would typically depend on the specific nature of the two markets and the goals of policy intervention.